Odpowiedzi

Najlepsza Odpowiedź!
2009-10-22T21:15:40+02:00
X = (1 - 2√3)² + (2 + √3)² - (3√3 - 2)(3√3 + 2) - 9
x=1-4√3+12+4+4√3+3-27+4-9
x=-12

y = 11 - 4 * 6 + 1/2
y=11-24+½
y=-12½

x>y
  • Użytkownik Zadane
2009-10-22T21:16:58+02:00
X = (1 - 2√3)² + (2 + √3)² - (3√3 - 2)(3√3 + 2) - 9=
(1²-2*1*2√3+(2√3)²)+(2²+2*2*√3+(√3)²)-[3√3*3√3+2*3√3-2*3√3-4]-9=
1-4√3+12+4+4√3+3-[27+6√3-6√3-4]-9=
20-23-9=-12
y = 11 - 4 * 6 + 1/2=11-24+1/2=-13+1/2=-26/2+1/2=-25/2=-12,5

Liczba y jest mniejsza od liczy x czyli y<x , -12,5 < -12